2017
DOI: 10.1111/jace.15176
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of phase relations and thermodynamic properties in the ZrO2–TiO2 system

Abstract: Phase relations in the ZrO 2 -TiO 2 system were studied experimentally using X-ray diffraction (XRD), scanning electron microscopy combined with dispersive X-ray spectrometry (SEM/EDX) and differential thermal analysis (DTA). The homogeneity ranges of ZrO 2 and TiO 2 , as well as high temperature disordered b-(Zr x Ti 1Àx ) 2 O 4 compound were defined in the temperature range of 1700-2040 K. Temperature and composition of eutectic reaction were measured. The standard enthalpy of formation of the b-ZrTiO 4 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The thermodynamically optimized phase diagram of the TiO 2 -ZrO 2 system according to experimental data [98] and data from other authors is shown in Fig. 5d.…”
Section: Tio 2 -Zro 2 Systemmentioning
confidence: 99%
“…The thermodynamically optimized phase diagram of the TiO 2 -ZrO 2 system according to experimental data [98] and data from other authors is shown in Fig. 5d.…”
Section: Tio 2 -Zro 2 Systemmentioning
confidence: 99%
“…To obtain reliable data on the TiO 2 activities in the binary TiO 2 ‐ZrO 2 system, the temperature of the sample vaporization had to be increased. The concentration dependence of the TiO 2 activities at the temperature 2356 K, Figure 7, and its comparison with the corresponding phase diagram of this system [10] suggested the existence of strong positive deviation from the ideal behavior in the concentration range from pure titania to equimolar composition of the TiO 2 ‐ZrO 2 system. As the titanium dioxide content in sample N 3, Table 1, decreased from the initial value of 66.7 mol .…”
Section: Discussionmentioning
confidence: 89%
“…The determined SiO 2 activity values enabled calculation of the SiO partial pressures at the temperature 1973 K over the samples under study by Equation (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, despite the fact that the phase formation in the ZrO 2 -TiO 2 system has being studied for a long time [32][33][34][35][36][37][38], but even today information about phase equilibria presented in the literature is not completely agreed (Fig. 1), in particular with respect to the com-position and structure of the compound, which was indicated in the phase diagram by Brown et al [34] for the first time (Fig.…”
Section: Introductionmentioning
confidence: 99%